Analisis Kondisi Sosial Ekonomi Masyarakat Kawasan Kumuh dan Perkembangannya Dalam Perspektif Rencana Tata Ruang Kota ( Kasus Studi : Kawasan Kumuh Kecamatan Bekasi Barat Kota Bekasi) - suhardi; Zefri (Journal of Urban and Regional Development Studies, 2024)
Many factors can affect the existence of slum areas. These factors include urbanization, infrastructure, economy, urban land, spatial planning, urban attractiveness, socio-cultural, building ownership status and length of stay. urban attractiveness, socio-cultural, building ownership status and length of stay of residents. occupants. From the description of the problem of slum areas in West Bekasi, the purpose of this study is to analyze the Socio-Economic conditions of the Slum Area Community and its Development When Viewed from the Aspects of the City Spatial Plan. To answer the problem formulation and objectives in this research, the researcher uses a Qualitative Method using a case study approach, which is intended to explore the socio-economic conditions of the community in the West Bekasi Slum Area, by means of interviews and observations during the research. The analysis tool used is through three stages: Data Reduction; Data Presentation and Conclusion Drawing or Verification. The research results of the Socio-Economic Condition Analysis of Communities in Bekasi City Slums are as follows: 1. The Socio-Economic Condition of the West Bekasi Slum Area, can be described as a poor neighborhood, due to low income levels, low education levels, odd jobs such as laborers, gojek drivers. The majority of residents are migrants from around outside Bekasi city; 2. From the aspect of ownership, most of them are self-owned, but some of their land status is not certified but is legal because it is in the form of girik. Due to low incomes, generally below Rp.1,000,000 per month, in addition to low education levels, their attention and knowledge are limited in maintaining a clean environmental lifestyle or free from slums; 3. There are three (3) important points that are of concern in dealing with socio-economic issues in the West Bekasi Slum, namely; a. Public awareness in the slum area, in terms of maintaining cleanliness and public order Rehabilitation efforts by the government (already underway) on the supporting infrastructure of a clean and healthy area, such as building conditions, environmental roads, drainage, garbage, green spaces and fire protection tools that must be available in the slum area; c. Efforts in the field of slum management, in a more humane manner and considering the best way out and in favor of the interests of the people living in the slum area and d. The analysis of the spatial plan, showing that the slum area is not only a slum area, but also a slum area. Taking into account the analysis of the spatial plan, it shows that explicitly the pattern and characteristics of slum areas are not contained in the Bekasi city spatial pattern plan in detail, but are described in the density of buildings in each sub-district including West Bekasi Sub-district